2011
DOI: 10.3758/s13423-011-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotional cues enhance the attentional effects on spatial and temporal resolution

Abstract: In the present study, we demonstrated that the emotional significance of a spatial cue enhances the effect of covert attention on spatial and temporal resolution (i.e., our ability to discriminate small spatial details and fast temporal flicker). Our results indicated that fearful face cues, as compared with neutral face cues, enhanced the attentional benefits in spatial resolution but also enhanced the attentional deficits in temporal resolution. Furthermore, we observed that the overall magnitudes of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
3
53
0
Order By: Relevance
“…For instance, it has been proposed that widening of attention and enhancing visual perception is adaptive in an evolutionary sense: Seeing a fearful face signals that an expresser may perceive threat in the environment, leading others to localize and identify any such threat themselves. These findings are in line with studies demonstrating benefits from viewing facial expressions of fear in the spatial and temporal domain as well as with regard to enhanced contrast sensitivity (Bocanegra and Zeelenberg, 2009a; Bocanegra and Zeelenberg, 2009b, 2011a; Bocanegra and Zeelenberg, 2011b; Phelps et al, 2006). In the same vein, the perception of fear increases efficiency in visual search, even for non-threatening objects (Becker, 2009), which was recently replicated in a study where prior exposure to a fearful expression resulted in faster target identification in a subsequent visual search task, compared to exposure to other facial expressions.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, it has been proposed that widening of attention and enhancing visual perception is adaptive in an evolutionary sense: Seeing a fearful face signals that an expresser may perceive threat in the environment, leading others to localize and identify any such threat themselves. These findings are in line with studies demonstrating benefits from viewing facial expressions of fear in the spatial and temporal domain as well as with regard to enhanced contrast sensitivity (Bocanegra and Zeelenberg, 2009a; Bocanegra and Zeelenberg, 2009b, 2011a; Bocanegra and Zeelenberg, 2011b; Phelps et al, 2006). In the same vein, the perception of fear increases efficiency in visual search, even for non-threatening objects (Becker, 2009), which was recently replicated in a study where prior exposure to a fearful expression resulted in faster target identification in a subsequent visual search task, compared to exposure to other facial expressions.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that covert attention by spatial precueing enhances spatial resolution (i.e., our ability to discriminate small details in a visual stimulus) in the absence of external noise (e.g., Bocanegra & Zeelenberg, 2011;Carrasco, Williams, & Yeshurun, 2002;Golla, Ignashchenkova, Haarmeier, & Their, 2004). This suggests that attentional effects on visual processing can be produced not through external-noise reduction and that attention can enhance perceptual representation of the stimulus at the attended location through finer spatial resolution.…”
mentioning
confidence: 85%
“…According to the authors, slower and sustained responses of parvo cells are selective for fine-grained HSF stimuli at high luminance contrast, whereas fast and transient responses of magno cells are selective for coarse LSF stimuli at low contrast. Especially in regard to the reciprocal connectivity between the magnocellular division of amygdala and visual cortices (Amaral, et al, 2003), an early facilitation of magnocellular processing induced by emotional stimuli may accompany an inhibition of parvocellular processing (Bocanegra & Zeelenberg, 2011). …”
Section: Emotion and Concurrent/subsequent Visual Processingmentioning
confidence: 99%